(untitled) (Neo Science Peer Reviewed Journal, 2023)
One of the urgent tasks of the current period is the love of the younger generation to the Motherland, loyalty, a sense of pride to our ancient and rich spiritual heritage, national and universal values educate in the spirit. The world community of the state of Uzbekistan with a growing economy as political and economic, cultural and educational ties with their countries expand together with the students’ interest in the economy, history, customs and language of foreign countries is growing. This thesis presents some of the ways to develop oral speech in English lessons dedicated to discussion. The main focus is dedicated teaching English to high school students. Interest of students in high schools, gymnasiums, universities and schools and development of their oral speech and vocabulary, taking into account their inclinations is important.